Enhancing Customer Experience through Artificial Intelligence: Opportunities and Challenges in Digital Marketing (A Study of Indian IT Companies) - Sen, Sujay (Digital Repository of Theses, 2025)
The study aims to enhance customer experience through artificial intelligence thereby assessing opportunities and challenges in digital marketing in India. The existing study is conducted in Bangalore, Chennai and Pune cities in India. The existing study is exploratory and primary. The study selected IT employees from three cities, namely, Bangalore, Chennai and Pune in India. The sample size of the existing study is 600 information technology (IT) employees. The study is based on purposive sampling technique. Various statistical techniques applied to assess the constructed questionnaire, namely, descriptive statistics, frequency, percentage, ANOVA, Regression, Correlation, one sample t test, Exploratory factor analysis and Chi-square test. The findings of the study analysed factors that influence AI-driven personalization on customer loyalty and trust in the digital marketing and stated that “Funding to support the choice for AI” found to be the most influencing factor that influence AI-driven personalization on customer loyalty and trust in the digital marketing. Additionally, the study assessed opportunities of AI in digital marketing operations in the organisation and stated that “AI for marketing management and worldwide advertising campaigns and multilingual content generation” is the most important opportunity of AI in digital marketing operations in the organisation. Then, the existing research analysed challenges of AI in digital marketing operations in the organisation and stated that “Decision making due to robotic integration can also be problematic mainly arising from compatibility issues with existing structures” is the most important challenge of AI in digital marketing operations in the organisation. Finally, the findings of the study assessed recommendations of developing long-term relationships and brand loyalty among customer through artificial intelligence enhanced digital experiences and documented that “Surround the adoption of AI in the organisation’s digital marketing plan with clarity on goals since the onset” is the most important recommendation of developing long-term relationships and brand loyalty among customer through artificial intelligence enhanced digital experiences.